Dynamic and Scalable Storage Management in Grid Environment - Kumar, Ajay (My University, 2010)
Grid applications typically deal with large amounts of data. In traditional approaches high-performance dedicated servers are used for data storage and data replication. Data storage management is one of the most challenging issues for Grid computing. As computational grid focuses on the usage of idle resources from interconnected machines, a large amount of unused storage space can be used when the machines are idle or underutilized. In this thesis new mechanism for Dynamic and Scalable Storage Management (DSSM) in grid environments is proposed. The storage can be transparently accessed from any grid machine, allowing easy data sharing among grid users and applications. The concept of virtual ids that, allows the creation of virtual spaces has been introduced and used.
M.E. (Software Engineering) Thesis
Keywords: Grid Computing; DSSM; Data management; AIT; GOS